Premature lethality, hyperactivity, and aberrant phosphorylation in transgenic mice expressing a constitutively active form of Fyn - Xia, Di; Götz, Jürgen (Frontiers in Molecular Neuroscience, 2014)
The kinase Fyn, the microtubule-associated protein tau and the peptide amyloid-β (Aβ) constitute a toxic triad in Alzheimer's disease. Tau's subcellular localization is mainly regulated by phosphorylation whereas Fyn's localization is dictated by palmitoylation targeting it to the plasma membrane in a reversible manner. We have previously shown that tau is required for Fyn to be targeted to the dendritic spine. We had also shown that a truncated form of tau (Δtau) that accumulates in the cell soma is capable of trapping Fyn and preventing it from entering the spine. Here we determined that palmitoylation is required for Fyn's membrane and spine localization. We further evaluated the functional consequences of neuronal over-expression of the constitutively active Y531F mutant form of Fyn (FynCA) in transgenic mice. We found that the FynCA transgenic mice displayed a reduced weight, a massively reduced life span and a high level of hyperactivity. The lifespan of the FynCA mice was only slightly extended by crossing them with Δtau transgenic mice, possibly reflecting differences in expression patterns of the transgenes and high levels of transgenic FynCA compared to endogenous Fyn. Analysis of synaptosomes revealed that FynCA accumulated at high levels in the spine, resulting in increased levels of the NMDA receptor subunit NR2b phosphorylated at residue Y1472. Tau was strongly phosphorylated at the AT8 epitope S202/T205 as shown by Western blot and immunohistochemistry indicating that an increased tyrosine kinase activity of Fyn has down-stream consequences for serine/threonine-directed phosphorylation.